2007
DOI: 10.1016/j.ejvs.2007.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The Symptoms of Varicose Veins: Difficult to Determine and Difficult to Study

Abstract: Symptoms are a common indication for treating varicose veins and it is therefore important to be sure that they are due to the veins, rather than other causes. This report highlights traditional and logical questions which may help to identify symptoms caused by varicose veins but illustrates the difficulty of validating them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 8 publications
1
23
0
1
Order By: Relevance
“…The response rate of 72% in this study is in line with other questionnaire studies including VV patients. 16,27,30 Questionnaires were administered by post which probably reduced the response rate, but prevented the social desirability bias associated with interview. Also, patients were unlikely to inflate their symptoms ("fake bad") in this study as they were already attending for treatment at the time of completing the questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…The response rate of 72% in this study is in line with other questionnaire studies including VV patients. 16,27,30 Questionnaires were administered by post which probably reduced the response rate, but prevented the social desirability bias associated with interview. Also, patients were unlikely to inflate their symptoms ("fake bad") in this study as they were already attending for treatment at the time of completing the questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…They may also represent patients in whom symptoms reported were unrelated to an underlying venous cause. However, due to the difficulties in correlating venous reflux with symptomatogy, 26,29 this is extremely difficult to assess.…”
Section: Discussionmentioning
confidence: 99%
“…Standing for long periods of time increases complaints related to CVD. 45 We found that cooling of legs of participants with larger calf circumference, also indicative of obesity and/or swelling, resulted in minimal improvements in QOL or symptom reduction. In general, individuals with swelling have reduced function and higher reports of pain and disability.…”
Section: Discussionmentioning
confidence: 70%